The Effect of Cartilage Lesion in the Lateral Compartment of the Knee on the Surgical Outcome of Medial Open-Wedge High Tibial Osteotomy - Moon, Hyun-Soo; Choi, Chong-Hyuk; Jung, Min; Park, Sang-Hoon; Lee, Dae-Young; Shin, Ju-Cheol; Kim, Sung-Hwan (The Journal of Knee Surgery, 2019)
The aim of this study was to identify the effect of cartilage lesion in the lateral compartment of the knee on the surgical outcome of medial open-wedge high tibial osteotomy (MOWHTO). A total of 172 consecutive patients who underwent MOWHTO were evaluated retrospectively. Among the patients who underwent second-look arthroscopic assessment, 30 patients with lateral compartment cartilage lesion (group 1: ≥ grade 2 cartilage lesion according to the International Cartilage Repair Society [ICRS] grading system) and 64 patients with normal or near-normal lateral compartment cartilage (group 2: grade 0 or 1 cartilage lesion according to the ICRS grading system) were included in the analysis. Each patient was evaluated for the following variables: clinical scores, radiographic osteoarthritis grade, and comparative measurement under arthroscopy. All clinical scores were similar between the two groups preoperatively and at the time of second-look operation. Group 1 showed a significantly higher osteoarthritis grade in the lateral compartment of the knee on the 30 degree flexed posteroanterior view according to the International Knee Documentation Committee grading system preoperatively (p = 0.005) and at the time of second-look operation (p = 0.002). In regard to the comparative measurement under arthroscopy, the size of cartilage lesion on the medial compartment decreased by time in both groups (p = 0.000), whereas the size of cartilage lesion on the lateral compartment increased by time in both groups (p = 0.004). However, the degree of change in the cartilage lesion size in each compartment of the knee over time did not significantly differ between the two groups. Regarding the cartilage lesion grade in the lateral compartment, there was no statistically significant difference in the frequency of deterioration between the two groups. As a result, the presence of cartilage lesion of ICRS grade 2 or 3 in the lateral compartment of the knee, either subtle or not detected during the preoperative evaluation, would not affect the surgical outcome of MOWHTO. This is a Level IV, therapeutic case series study.
Keywords: medial open-wedge high tibial osteotomy; knee; lateral compartment of the knee; cartilage lesion